転炉内二次燃焼に及ぼす炉内水素濃度の影響 - 奥山, 悟郎; 山下, 博史; 山田, 敏雄; 林, 直樹; 岸本, 康夫; 山本, 和弘 (鉄と鋼, 2011)
In this study, numerical simulation of high temperature combustion in CO–H2 mixture with oxygen jet has been conducted to consider post combustion in a converter for steel making process. In the numerical model, a detailed reaction model and mixture fraction model were used. The flammability characteristics and flame structure were compared between both calculation results. The influence of H2 content in the mixture and the reaction mechanism of the combustion were discussed. In mixture fraction model, the post combustion ratio decrease with an increase of H2 content, but the influence of H2 content on post combustion ratio is small. On the other hand, in the detailed reaction model, the influence H2 content on post combustion ratio is bigger, and the post combustion ratio takes its maximum when the molar hydrogen concentration is 2%. When the molar hydrogen concentration is 20% in CO–H2 mixture, CO2 is decomposed around the edge of combustion zone, where the endothermic reaction occurs. Resultantly, the temperature in the downstream region is reduced. In the CO–H2 combustion, water vapor is also decomposed by the shift reaction through CO+H2O→CO2+H2.